How to De-Dollarize Financial Systems in the Caucasus and Central Asia? - Ben Naceur, Sami (IMF Working Papers; Working Paper ;, 2015)
Dollarization rates in the Caucasus and Central Asia (CCA) region are among the highest in the world, with adverse consequences for macroeconomic stability, monetary policy transmission, and financial sector development. Using dynamic panel data models, we find that foreign exchange deposits and loans in the CCA are mainly driven by volatile inflation and exchange rates, low financial depth, and asymmetric exchange rate policies biased toward depreciation. Although there is no unique formula for success, empirical studies and cross-country experiences suggest that credible monetary and exchange rate frameworks, low and stable inflation, and deep domestic financial markets are essential ingredients of any de-dollarization strategy. In implementation, policymakers need to consider proper sequencing of policies, effective communication as well as risks from potential financial disintermediation and instability, and/or capital flight.